Nurse-performed ultrasound assessment of gastric residual volume and enteral nasogastric tube placement in the general intensive care unit. (April 2022) - Brotfain, Evgeni; Erblat, Alexander; Luft, Peter; Elir, Adina; Gruenbaum, Benjamin F.; Livshiz-Riven, Ilana; Koyfman, Anna; Fridrich, Danielle; Koyfman, Leonid; Friger, Michael; Grivnev, Ana; Zlotnik, Alexander; et al.
Abstract: Objective: Ultrasonography is an essential imaging modality in the critical care population and has been increasingly utilized to check gastric residual volume . Various studies have shown that intensive care unit nurses untrained in ultrasound can easily be trained in its accurate interpretation. We prospectively analyzed nurse-performed repeated measurements of gastric residual volume and nasogastric tube positioning via an ultrasound technique in the intensive care unit. Design: This was a single-center, cross-sectional prospective study. Four intensive care unit nurses, evenly divided into two groups (teams A and B), underwent four hours of formal ultrasound training by three critical care staff physicians. The trained nurses provided bedside ultrasound assessments of gastric residual volume and nasogastric tube positioning which were compared to a standard protocol of syringe aspiration. Results: Ninety patients were recruited to the study. Four measurements per patient were performed, for a total of 360 assessments. The ultrasound gastric residual volume assessments were correlated with the syringe aspiration protocol and demonstrated high Intraclass Correlation Coefficient rates of 0.814 (0.61–0.92) for team A and 0.85 (0.58–0.91) for team B. Nasogastric tube placement was successfully and independently verified by ultrasound in most of the critically ill patients (78% of team A and 70% of team B). The comparative ultrasound assessments of tube positioning demonstrated good correlation of 0.733 (0.51–0.88) between each team's two independent observers. Conclusion: Our study demonstrated a strong correlation between US utilization for assessment of gastric residual volume and nasogastric tube positioning and standard protocol methods, suggesting it is a safe, simple and effective practice for intensive care unit nurses.